Continuing education: contributions to the pedagogical practice of nurses (Research, Society and Development, 2020)
Objective to reflect on continuing education as a contribution to the pedagogical practice of nurses in professional education. Study of qualitative approach of bibliographic research, which considered the works, Pedagogy of the Oppressed and Pedagogy of Autonomy, both by Paulo Freire. For such reflection, the following category was chosen: Nursing pedagogical practice and permanent formation in Freire. Thus, although nurses are educators and the undergraduate nursing enables broad performance, from the area of care to teaching in vocational technical education, it is understood that it is necessary for nurses to have a permanent training on pedagogical issues. Continuing education contributes to the pedagogical practice of nurses, when it makes it possible to rethink their own praxis. However, for this, it is necessary to know the fundamentals that guide a qualified action of teaching, which occurs through a pedagogical formation that allows broadening the traditional view of teaching and that considers the student as responsible for their own formation, dialoguing, questioning and enabling critical reflection on what is taught.